DIABETIC FOOT ULCER PREVENTION THROUGH WORKPLACE WELLNESS PROGRAMS: CONCEPTUAL PERSPECTIVE (Social Security Management Journal, 2024)
Diabetes Mellitus in one of non-communicable disease (NCDs) and is a major public health problem in Malaysia, especially type 2 diabetes. International Diabetes Federation in 2019 reported, 463 million people infected with diabetes, projected to infect 578 million and 700 million of people by the year 2030 to 2045. One of the complications from DM were Diabetic Neuropathy, a nerve damage that can causes numbness, pain, and weakness, especially in the legs and feet. Diabetes Foot Ulcers (DFU) are a major complication in DM patients. Diabetic foot ulceration is a devastating complication of diabetes that is associated with infection, amputation, and death, and is affecting increasing numbers of patients with diabetes mellitus. Thus, this paper explores the conceptual framework for preventing DFUs through workplace wellness programs, emphasizing the integration of health education, risk factor management, and supportive environments. Workplace wellness initiatives can play a crucial role in educating employees about foot care practices, encouraging regular foot inspections, and promoting appropriate footwear. Key strategies include continuous education on glycemic control, lifestyle modifications, and the importance of early intervention for risk factors such as peripheral neuropathy and vascular disease. By fostering a culture of health and wellness in the workplace, organizations can significantly reduce the incidence of DFUs and improve overall employee health outcomes.